Identification of denudation periods and thickness in petroliferous basins and their geological significance: A case study of the central Sichuan Basin - Jingdong Liu; Shaohua Wang; Ke Pan; Chenggang Ren; Qihang Zhang; Jianting Xu (Energy Geoscience)
Restoration of denudation thickness is of great significance to understanding tectonic evolution, hydrocarbon migration and accumulation history in petroliferous basins. How to accurately restore and distinguish denudation thicknesses in different periods, however, is difficult. With measurements of vitrinite reflectance (Ro) and interval transit time, along with stratigraphic profile comparison, we restored the total denudation thickness of the Cretaceous in the central Sichuan Basin at a depth range of 1100–3300 m. The apatite fission track analysis (AFTA) was employed to identify the denudation periods, namely, the Late Yanshanian, Early Himalayan and the Late Himalayan orogenic epochs, and the ratio of their denudation intensity is about 3.8:1:3.9. The denudation thicknesses at different periods provide an important basis for tectonic evolution and hydrocarbon migration and accumulation. Affected by the diverse denudation intensities, the paleo-structures in the study area feature high in the south and low in the north at the Late Jurassic, high in the north and low in the south at the late Early Cretaceous, high in the southeast and low in the northwest at present in succession. EW- and NE-trending folds and faults are the products of inherited development, which have a controlling effect on hydrocarbon migration and accumulation.